2020
DOI: 10.2147/ijgm.s288067
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors Associated with Coronavirus Disease 2019 Prevention Practices in Three Zones of Southwest Ethiopia: Community-Based Cross-Sectional Study</p>

Abstract: Background The cases of coronavirus disease 2019 (COVID-19) and related deaths are increasing exponentially in Ethiopia. Prevention is currently available effective management, and its implementation has not been assessed adequately. This study aimed to identify the factors associated with COVID-19 prevention practices in three zones of southwest Ethiopia. Methods A community-based cross-sectional study was conducted in the Bench Sheko, Kafa, and West Omo zones. A multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“… 19 Our result also revealed that those who have a family size of ≥4 were 2.06 more likely to have good preventive practice towards COVID-19 infection than those who had a family size of less than four which was supported by finding in Southwest Ethiopia. 20 However as a limitation, in this study we estimated only socio-demographic factors and we might miss controlling other variables which may affect the result.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 19 Our result also revealed that those who have a family size of ≥4 were 2.06 more likely to have good preventive practice towards COVID-19 infection than those who had a family size of less than four which was supported by finding in Southwest Ethiopia. 20 However as a limitation, in this study we estimated only socio-demographic factors and we might miss controlling other variables which may affect the result.…”
Section: Discussionmentioning
confidence: 96%
“…a family size of less than four which was supported by finding in Southwest Ethiopia. 20 However as a limitation, in this study we estimated only sociodemographic factors and we might miss controlling other variables which may affect the result.…”
mentioning
confidence: 96%
“…The level of education was also reported as a significant factor in the study conducted in Sidama and Tigrai regions of Ethiopia. 11 12 Moreover, studies done in South West Ethiopia, 13 Tigrai 12 and Palestine 14 added that level of knowledge is a significant factor of COVID-19 prevention. This indicated that level of awareness is important to prevent the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was reported by a study done in South West Ethiopia. 13 This may be due to familial responsibilities to prevent the disease and opportunities to discuss the disease.…”
Section: Discussionmentioning
confidence: 99%
“…About 79% of Ethiopia are inhabitant of rural areas with poor road network, weak transportation and communication links. 38 RCCE task forces have been set up at the lowest administrative units and at health facilities to reach hard-to-reach communities. 36 These units involve the country’s forty-two thousand health extension workers, with two per village, who undertake the task of sensitization and awareness creation.…”
Section: Methodsmentioning
confidence: 99%